Science in Argentine newspapers: issues and journalistic production in generalist press (2015) - Spina, Guillermo Damián (2017)
This article examines the production of news about science in general newspapers in Argentina. There are distinguished dimensions of the status of journalistic treatment as subjects, genres and production forms as from content analysis on a representative sample week built in 2015. For the purposes of determining regularities and peculiarities in the volume and deployment informative, partial results that help to describe the characteristics of publication’s production that make public communication of science are exposed. As an hypothesis it is argued that are predominant those issues whose scientific innovation represents a social benefit (eg health) and the utilization of the announcement format, which requires less informative production by the media analyzed.